2016
DOI: 10.1371/journal.pone.0166329
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Evaluation of Human Papillomavirus Type Competition and the Potential for Type Replacement Post-Vaccination

Abstract: BackgroundMillions of women have been vaccinated with one of two first-generation human papillomavirus (HPV) vaccines. Both vaccines remain in use and target two oncogenic types (HPVs 16 and 18); however, if these types naturally compete with others that are not targeted, type replacement may occur following reductions in the circulating prevalence of targeted types. To explore the potential for type replacement, we evaluated natural HPV type competition in unvaccinated females.MethodsValid HPV DNA typing info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 47 publications
0
15
2
Order By: Relevance
“…The prevalence ratios [PR with 95% confidence interval (CI)] of specific HPV types (HPV6, 11,16,18,31,33,35,39, 45, What's new? Vaccination against high-risk human papilloma virus (HPV) strains is efficacious, but possible resurgence of non-targeted viral strains is a concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence ratios [PR with 95% confidence interval (CI)] of specific HPV types (HPV6, 11,16,18,31,33,35,39, 45, What's new? Vaccination against high-risk human papilloma virus (HPV) strains is efficacious, but possible resurgence of non-targeted viral strains is a concern.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, thus far HPV type-replacement has not been observed at the individual level among HPV vaccinated females with low vaccination coverage in the target population. [10][11][12] Implementation of national HPV vaccination programs, however, tends to increase prevalence of some non-vaccine covered HPV types suggesting type-replacement. [10][11][12] Implementation of national HPV vaccination programs, however, tends to increase prevalence of some non-vaccine covered HPV types suggesting type-replacement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Therefore, several studies evaluating the possibility of HPV type replacement have focussed on finding competitive interactions among HPV types. [46][47][48] Nevertheless, even in the absence of competition mechanisms, the results of this study show that type replacement is viable at the within-host level if the degree of cross-protection induced by the vaccine is not high enough. Type replacement has been observed following vaccination in Durham et al 39 In this study, the authors reported that the prevalence of HPV types phylogenetically related to HPV-16 (types 39, 45, 59, and 68) and HPV-18 (types 39, 45, 59, and 68) increased by 50% and 29% following vaccination, respectively.…”
Section: Discussionmentioning
confidence: 77%
“…Pooling data from five pre-vaccination epidemiological studies, including HITCH, and applying a hierarchical Bayesian regression approach that employs shrinkage and adjustment for confounders (i.e., age and lifetime number of sex partners) and other HPV types, we found HPV16 to be the most common type (prevalence range: 1.0% to 13.8%) [32]. HPV types were more likely to be detected as part of a multiple infection than as single infections.…”
Section: Natural Hpv Type Competition In Unvaccinated Femalesmentioning
confidence: 94%